"Decision for adjuvant treatment in stage II colon cancer based on circulating tumor DNA:The CIRCULATE-PRODIGE 70 trial". Issue 7 (July 2020) - Taïeb, Julien; Benhaim, Léonor; Laurent Puig, Pierre; Le Malicot, Karine; Emile, Jean François; Geillon, Flore; Tougeron, David; Manfredi, Sylvain; Chauvenet, Marion; Taly, Valerie; Lepage, Côme; André, Thierry
Abstract: Background: Adjuvant treatment for stage II colon cancer remains debated. Finding a tool to select patients at risk for disease recurrence may help the clinical decision. Circulating tumor DNA (ctDNA) has been reported recently as a potential predictive marker for disease recurrence. We thus aim to test its ability to better select stage II colon cancer patients for adjuvant therapy. Methods: This national, phase III trial (NCT 2019-000935-15) conducted in more than 100 centers in France, plans to screen around 2640 patients in order to randomize (2:1; minimization method) 198 ctDNA positive patients. Patients aged 18 to 75 years with ECOG performance status ≤1 with R0 surgical resection of a pT3-T4aN0 colon or high rectum adenocarcinoma will be randomized within 63 days after curative-intent surgery, to adjuvant mFOLFOX6 (oxaliplatin 85 mg/m², leucovorin 400 mg/m², and 5-FU bolus 400 mg/m2 then 5FU Continuous infusion 2.4 g/m²) every two weeks for 12 cycles or observation. Patients will be followed for maximum 7 years. A gain of 17.5% in 3-yr disease free survival (DFS) is expected (42.5% in the experimental arm vs. 25% in the control arm; HR:0.62; α, 5% [two-sided log-rank test]; 1-β, 80%). Secondary endpoints include 2-yr DFS, overall survival, and toxicity. Recruitement began End of January 2020.